2020
DOI: 10.1111/bjop.12450
|View full text |Cite
|
Sign up to set email alerts
|

Elite stigmatization of the unemployed: The association between framing and public attitudes

Abstract: This paper uses a multi‐methods approach to explore the social psychological construction of stigma towards the unemployed. Study 1a uses thematic analysis to explore frames used by political elites in speeches at U.K. national party conferences between 1996 and 2016 (n = 43); in study 1b, we track the usage of these frames in six national newspapers (n = 167,723 articles) over the same period showing an increase in the use of negative frames. Study 1c shows that these are associated with national attitudes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…In other words, we identified and counted all the articles on the topic published in all the available newspapers in the three countries and indexed in the Factiva database. Moreover, following Okoroji et al (2021), we obtained a proxy for the total newshole published in each country over the period by searching for the word "the" (India,n = 37,828,031;Italy,n = 45,295,616;the UK,n = 98,257,528).…”
Section: Constructing a Text Corpusmentioning
confidence: 99%
“…In other words, we identified and counted all the articles on the topic published in all the available newspapers in the three countries and indexed in the Factiva database. Moreover, following Okoroji et al (2021), we obtained a proxy for the total newshole published in each country over the period by searching for the word "the" (India,n = 37,828,031;Italy,n = 45,295,616;the UK,n = 98,257,528).…”
Section: Constructing a Text Corpusmentioning
confidence: 99%
“…For example, Moussa-Smona [80] found that economically vulnerable people have a lower level of subjective well-being and life satisfaction than those who are more secure. Similarly, Okoroji et al [62] showed that stigmatization processes produced by representations in media and politics make poor people suffer from marginalization, which in turn causes vulnerability for psychological distress. Another study demonstrates that social injustice and poverty increases negative child experiences [82].…”
Section: Outcomes Of Povertymentioning
confidence: 99%
“…Guzzo [61] also emphasizes that psychological inquiry should focus on the political attitude when combating poverty. On the other hand, Okoroji et al [62] prioritize the importance of the social-psychological analysis of marginalization towards the poor addressing the relationship of poverty with the representations produced in the media and politics is expressed. Many studies that focus on the multidimensional evaluation of poverty also point to suggestions for reducing or ending poverty.…”
Section: Poverty As a Processmentioning
confidence: 99%
“…The Coalition's austerity programme took, in part at least, the symbolic 'form of a massive propaganda exercise' (Tyler, 2020: 194). From 2008, pejorative, stigmatising portrayals of out-of-work populations became increasingly prevalent in political discourse (Okoroji et al, 2020). Politicians intentionally rehashed and enflamed centuries' worth of 'scrounger' discourses to fortify anti-welfare common sense and manufacture consent for austerity (Morrison, 2019: 8;Tyler, 2020: 19).…”
Section: Welfare Propaganda: Cultivating a Hostile Environmentmentioning
confidence: 99%
“…This resulted in outbreaks of interpersonal violence upon migrant and benefit claiming populations (Burnett, 2017: 220;Ryan, 2019: 29). However, the main effects were a general hardening of public attitudes towards claimants and growing support for punitive measures (Okoroji et al, 2020). According to one survey, the percentage of people agreeing that cutting welfare benefits would damage too many people's lives had fallen by 17% from 59% in 2000 to 42% in 2010 (Taylor and Taylor-Gooby, 2014: 6).…”
Section: Welfare Propaganda: Cultivating a Hostile Environmentmentioning
confidence: 99%